Are the Things Told to Care Providers Kept Confidential?: Perceived Breaches of Confidentiality and Associated Factors Among HIV/AIDS Clients on ART at Nekemte Specialized Hospital, Western Ethiopia, 2021 - Bayisa L; Wakuma B; Abera T; Mulisa D; Mosisa G; Tolossa T; Turi E (HIV/AIDS: Research and Palliative Care, 2022)
Lami Bayisa,1 Bizuneh Wakuma,2 Tesfaye Abera,1 Diriba Mulisa,1 Getu Mosisa,1 Tadesse Tolossa,3 Ebisa Turi3 1Department of Nursing, School of Nursing and Midwifery, Institute of Health Sciences, Wollega University, Nekemte, Ethiopia; 2Department of Pediatric Nursing, School of Nursing and Midwifery, Institute of Health Sciences, Wollega University, Nekemte, Ethiopia; 3Department of Public Health, Institute of Health Sciences, Wollega University, Nekemte, EthiopiaCorrespondence: Lami BayisaDepartment of Nursing, School of Nursing and Midwifery, Institute of Health Sciences, Wollega University, PO Box 395, Nekemte, EthiopiaTel +251924318135Email lamisabayisa@gmail.comIntroduction: HIV clients’ mistrust in providers’ handling of their medical information can be a reason for them not to utilize services. Compromised confidentiality of HIV clients can affect the entire community, as other people may become reluctant to seek HIV testing and counseling. In Ethiopia, there are few data on perceived breaches of confidentiality among HIV/AIDS clients. Thus, this study aimed to assess perceived breaches of confidentiality and associated factors among people living with HIV (PLHIV) on anti-retroviral therapy (ART) at Nekemte Specialized Hospital, Western Ethiopia.Methods: A facility-based cross-sectional study was conducted among 423 HIV/AIDS clients at Nekemte Specialized Hospital from January 15 to February 20, 2021. Data were collected by an investigator-administered questionnaire. Collected data were entered into EpiData version 3.1, and Stata version 14.0 was used for analysis. Bivariable and multivariable logistic regression analyses were performed. Variables with a P-value of < 0.2 in the bivariable analysis were exported to the multivariable analysis. Adjusted odds ratios (AORs) with 95% confidence intervals (CIs) and P-values of < 0.05 were used to report significantly associated variables.Results: A total of 423 PLHIV were included in the study. Nearly one-fourth of the respondents (23.60%) had perceived breaches of confidentiality (95% CI 19.8– 27.9%). Delayed ART start [(AOR 1.97) 95% CI (1.05– 3.71)], being female [(AOR 4.03) 95% CI (2.14– 7.59)], being widowed [(AOR 4.11) 95% CI (1.50– 11.20)], college education and above [(AOR 10.89) 95% CI (3.93– 30.14)], normal BMI [(AOR 2.72) 95% CI (1.06– 6.99)], substance use [(AOR 1.93) 95% CI (1.04– 3.58)], not knowing other ART user(s) [(AOR 2.89) 95% CI (1.53– 5.47)], and CD4 count ≤ 200 cells/mm3 [(AOR 2.63) 95% CI (1.22– 5.68)] were significantly associated variables.Conclusion: One in four HIV/AIDS clients reported experiencing perceived breaches of confidentiality. Thus, early ART initiation, further HIV serostatus disclosure, and encouraging patients to decide on the type of care and information they want need to be strengthened in order to reduce breaches of confidentiality.Keywords: breaches of confidentiality, ART initiation, care providers, HIV/AIDS clients, PLHIV